Low-ionization structures in planetary nebulae – II. Densities, temperatures, abundances, and excitation of six PNe. Issue 3 (27th September 2022) - Mari, M Belén; Gonçalves, Denise R; Akras, Stavros
ABSTRACT: Here we present the spatially resolved study of six Galactic planetary nebulae (PNe), namely IC 4593, Hen 2-186, Hen 2-429, NGC 3918, NGC 6543, and NGC 6905, from intermediate-resolution spectra of the 2.5 m Isaac Newton Telescope and the 1.54 m Danish telescope. The physical conditions (electron densities, N e, and temperatures, T e ), chemical compositions and dominant excitation mechanisms for the different regions of these objects are derived, in an attempt to go deeper on the knowledge of the low-ionization structures (LISs) hosted by these PNe. We reinforce the previous conclusions that LISs are characterized by lower (or at most equal) N e than their associated rims and shells. As for the T e, we point out a possible different trend between the N and O diagnostics. T e [N ii ] does not show significant variations throughout the nebular components, whereas T e [O iii ] appears to be slightly higher for LISs. The much larger uncertainties associated with the T e [O iii ] of LISs do not allow robust conclusions. Moreover, the chemical abundances show no variation from one to another PN components, not even contrasting LISs with rims and shells, as also found in a number of other works. By discussing the ionization photon flux due to shocks and stellar radiation, we explore the possible mechanisms responsible for the excitation of LISs. We argue that the presence of shocks in LISs is not negligible, although there is a strong dependence on the orientation of the host PNe and LISs.